Teachers’ Social Construction Towards the Learning of Curriculum 2013 in Primary Schools - Febriane, Tiara Vera; Ajmaja, Hamdan Tri; Setiawan, Deni (Journal of Primary Education, 2021)
Preliminary understanding of Curriculum 2013 becomes reference for teachers in teaching. Different knowledge and backgrounds of teachers about curriculum 2013 in primary cause the learning process also to get diverse. So, the teachers’ social construction is also different. This study aims to analyse teachers’ social construction and the school preparation in implementing curriculum 2013. This study used phenomenological approach. The data collection technique was done by interviews, observations, and document studies on grade I–V teachers and principals, which validity has been tested through the data collection method, data reduction, data presentation and conclusion drawing. The results showed there are three categories of social construction towards curriculum 2013, due to the different processes of teaching experience and training. First, teachers construct curriculum 2013 as a complement for better purpose of education. Second, teachers construct curriculum 2013 as a teaching reference with difficulties. Third, teachers construct curriculum 2013 as a substitute of previous curriculum. The school readiness has designed in detail and prepared by; carrying out socialization for school residents, training and tutoring program for teachers and principals, completing learning tools, then conducting monitoring and evaluation, as well as the facilities and infrastructures that are supportive for the learning process.